Design and Analysis of Double Crank Type Climbing Mechanism - Zhanli Li Shuang Chen Yanwei Ji Chuntian Lu Guanhong Wang (Jixie chuandong, 2019)
Through the comparative analysis of the climbing mechanism of stair climbing wheelchair， a double crank type climbing mechanism is proposed. The design and research of the double crank type climbing mechanism is studied， and the kinematics model of the double crank climbing mechanism is established. Based on this， an analysis of the motion trajectory during the climbing process is carried out. The simulation results show that the structure of the climbing mechanism is reasonable， the scheme is feasible and the operation is stable to meet the design requirements.